Acute kidney injury secondary to tubo-ovarian abscess: A case report - X. Yin; Z.Y. Wang; Y. Yao (Clinical and Experimental Obstetrics & Gynecology, 2020)
Acute kidney injury secondary to tubo-ovarian abscess is rare. Here, we present a case of acute kidney injury arising from urethral obstruction secondary to a tubo-ovarian abscess. A 49 year old woman with complaints of persistent fever and abdominal pain was transferred to our hospital. A transvaginal ultrasound revealed two large pelvic masses that were suspected of being bilateral tubo-ovarian abscesses. During broad spectrum parenteral antibiotic treatment, the patient reported oliguria. With no response to fluid resuscitation and renal replacement treatment, we performed a laparoscopic bilateral salpingo-oophorectomy to relieve the urethral obstruction. Surgical removal of the bilateral tubo-ovarian abscess was effective in this patient.